2020
DOI: 10.1055/a-1144-3175
|View full text |Cite
|
Sign up to set email alerts
|

Curve Sprinting in Soccer: Kinematic and Neuromuscular Analysis

Abstract: Sprinting in curvilinear trajectories is an important soccer ability, corresponding to ~85% of the actions performed at maximum velocity in a soccer league. We compared the neuromuscular behavior and foot contact-time between outside leg and inside leg during curve sprinting to both sides in soccer players. Nine soccer players (age=23±4.12 years) performed: 3×Sprint linear, 3×Sprint right curve, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 26 publications
3
42
0
Order By: Relevance
“…Previous studies [12,13] also detected strong correlations ranging from 0.74 to 0.82 in young male soccer players. The nearly perfect relationships observed herein may suggest that higher-level players (i.e., professional, and national team athletes) are able to better express and utilize their linear sprint capacity over curvilinear paths, possibly through an optimized action of the inside leg (considered the main limiting factor when sprinting over curved trajectories) and a superior ability to cope with high centripetal forces [13,[25][26][27][28]. In a sample of semi-professional soccer players, Filter et al [26] demonstrated that the inside and outside legs present different behaviors and kinematic patterns during CS actions.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Previous studies [12,13] also detected strong correlations ranging from 0.74 to 0.82 in young male soccer players. The nearly perfect relationships observed herein may suggest that higher-level players (i.e., professional, and national team athletes) are able to better express and utilize their linear sprint capacity over curvilinear paths, possibly through an optimized action of the inside leg (considered the main limiting factor when sprinting over curved trajectories) and a superior ability to cope with high centripetal forces [13,[25][26][27][28]. In a sample of semi-professional soccer players, Filter et al [26] demonstrated that the inside and outside legs present different behaviors and kinematic patterns during CS actions.…”
Section: Discussionmentioning
confidence: 82%
“…The nearly perfect relationships observed herein may suggest that higher-level players (i.e., professional, and national team athletes) are able to better express and utilize their linear sprint capacity over curvilinear paths, possibly through an optimized action of the inside leg (considered the main limiting factor when sprinting over curved trajectories) and a superior ability to cope with high centripetal forces [13,[25][26][27][28]. In a sample of semi-professional soccer players, Filter et al [26] demonstrated that the inside and outside legs present different behaviors and kinematic patterns during CS actions. The inside leg displays higher contact times and resembles a "continuum cross-step maneuver," while the outside leg displays shorter ground contact times and exhibits an action similar to a "continuum side-step maneuver" [26].…”
Section: Discussionmentioning
confidence: 82%
“…The main use of the mDurance is the muscle assessment for clinics and sports professionals, due to its low price, low weight and automated signal processing. Typical situations to use mDurance could be the clinical evaluation of low back pain through the endurance test (Banos et al, 2015 ) or the flexion-relaxation phenomenon (Carrillo-Perez et al, 2018 ), and the neuromuscular assessment of the curve sprint in football at high intensity, in the field of sport biomechanics (Filter et al, 2020 ). Nevertheless, the use of a non-validated novel sEMG system could be harmful to the health of patients or affect the performance of athletes, due to potential misinterpretations.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the findings reported in previous studies, it seems logical that asymmetries between CS and COD-90 ⍛ will exhibit opposite directionality in most soccer players analyzed. In fact, most compelling evidence is in favor of the greater contribution of the outside leg during COD tasks ( Young et al, 2002 ), and the inside leg during curvilinear sprints ( Chang and Kram, 2007 ; Filter et al, 2020 ). Young et al (2002) concluded that the outside leg would exert more influence than the inside leg in turning movements if the movements require a “clear lateral push-off action” (i.e., COD-90 ⍛ ).…”
Section: Discussionmentioning
confidence: 99%
“…Young et al (2002) concluded that the outside leg would exert more influence than the inside leg in turning movements if the movements require a “clear lateral push-off action” (i.e., COD-90 ⍛ ). Conversely, during maximum effort, a reduction in peak resultant ground reaction force by the inside leg plays a significant role in limiting speed during curvilinear paths ( Chang and Kram, 2007 ; Filter et al, 2020 ). Furthermore, this study obtained a higher relationship between COD and CS on opposite sides than on equal sides ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%